Motivation, Engagement, and Mathematics Achievement: An Exploratory Study Among Chinese Primary Students. (November 2022) - Xia, Qi; Yin, Hongbiao; Hu, Ruonan; Li, Xiuhan; Shang, Junjie
Student motivation and engagement have been complex issues in basic mathematics education. Based on the theory of Motivation and Engagement Wheel, this study examined the relationships among student motivation, engagement, and mathematics achievement. A sample of 1, 538 Chinese primary school students participated in the survey, and motivation and engagement were assessed through their responses to the Motivation and Engagement Scale. The results largely confirmed the hypothesized relationships between motivation, engagement, and mathematics achievement. Some consistent patterns of individual differences related to gender and grade level were also revealed. Cluster analysis revealed that the category of "struggling students" showed high levels of adaptive engagement in learning, but their mathematics scores were still low, which may be correlated to their high level of maladaptive motivation and engagement. These findings provide implications for developing a more comprehensive knowledge of the nature of students' mathematics learning motivation and improving their engagement in mathematic learning.